2016
DOI: 10.3945/jn.116.239509
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Vitamin D and Cardiovascular Disease Risk Factors in African Americans Are Partly Explained by Circulating Adipokines and C-Reactive Protein: The Jackson Heart Study

Abstract: Background: Although it is recognized that vitamin D deficiency is associated with cardiovascular disease (CVD) risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The anti‐inflammatory actions of vitamin D discussed earlier, including the regulation of NF‐κB and down‐regulation of pro‐inflammatory cytokines such as IL‐6, may also protect against atherosclerosis. This is supported by the large epidemiological Jackson's Heart Study of CVD risk factors in African–Americans, which showed that the relationship between vitamin D and CVD was partially mediated through C‐reactive protein and adipokines.…”
Section: Vitamin D and Cardiovascular Diseasesmentioning
confidence: 80%
“…The anti‐inflammatory actions of vitamin D discussed earlier, including the regulation of NF‐κB and down‐regulation of pro‐inflammatory cytokines such as IL‐6, may also protect against atherosclerosis. This is supported by the large epidemiological Jackson's Heart Study of CVD risk factors in African–Americans, which showed that the relationship between vitamin D and CVD was partially mediated through C‐reactive protein and adipokines.…”
Section: Vitamin D and Cardiovascular Diseasesmentioning
confidence: 80%
“…However, other researchers found no significant difference in the circulating adiponectin concentrations between PCOS and non-PCOS groups [34] , and such discrepancy could be related to the ethnic and demographic variations among the studied populations [34] . Toward this latter suggestion, positive correlations of systemic vitamin D status with circulating adiponectin, and hypoadiponectinemia is a link between hypovitaminosis D and IR, have been detected among diabetic Saudi patients [39] and also among African American patients with cardiovascular disease [40] .…”
Section: Discussionmentioning
confidence: 99%
“…(3) Hypovitaminosis D may have an adverse effect on endothelial function and eventually lead to an increased stiffness of the aorta [ 48 ]. (4) Vitamin D can improve insulin secretion by activating vitamin D receptors in pancreatic islet β -cells [ 49 ]. In the present study, 25(OH)D is associated with HOMA-IR, HOMA- β , and RBP4, and after vitamin D therapy, the three indexes were all improved.…”
Section: Discussionmentioning
confidence: 99%